Effect of heat treatment on corrosion resistance of DMLS AlSi10Mg alloy. (10th July 2016) - Cabrini, M.; Lorenzi, S.; Pastore, T.; Pellegrini, S.; Ambrosio, E.P.; Calignano, F.; Manfredi, D.; Pavese, M.; Fino, P.
Abstract: The paper deals with the effect of heat treatments on corrosion resistance of an AlSi10Mg alloy obtained by means of Direct Metal Laser Sintering. The tests were performed on as-processed alloy and after different post-heat treatment, covering stress relieving, annealing at high temperature and water quenching. Potentiodynamic and electrochemical impedance spectroscopy tests were carried out in aerated Harrison solution. The results show localized corrosion and selective penetrating attack at the border of melt pools on untreated or only stress relieved specimens. The selective attack was not observed after high temperature annealing. Modification of EIS plot evidenced galvanic coupling with silicon coarse particles that extensively precipitate during high temperature annealing. The morphology of precipitates is described in order to evidence their relevance in terms of rising selective penetrating attack and galvanic coupling.